(untitled) (Hematology Meeting Reports, 2009)
Gemcitabine (2’,2’-difluorodeoxycytidine, dFdC) is an analog of deoxycytidine. It is transformed to the active triphosphate(dFdCTP) after intracellular phosphorylation. Gemcitabine monophosphate is inserted into the DNA and inhibits DNA elongation as a false nucleotide. In contrast to other antimetabolites, an additional, altered nucleotide is inserted behind dFdC inhibiting repair mechanisms (masked chain termination). By this, repair enzymes (exonucleases) of the DNA are inhibited and repair mechanisms are prevented. This factor, as well as enzymic inhibition of gemcitabine diphosphate, lead to high intracellular concentrations of gemcitabine and enforce the cytostatic effect. Gemcitabine is mostly inserted into DNA but partly also into RNA. Competition at the receptor with the nucleoside deoxycytidine phosphate (dCTP) leads to a competitive inhibition of DNA polymerases.1